2015
DOI: 10.1111/jdv.13028
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and anthropological perspectives on chemical relaxing of afro‐textured hair

Abstract: The culturally engrained practice of 'relaxing' afro-textured hair has been linked with hair and scalp disorders. Herein, we discuss the evolution of human hair types, focusing in particular on afro-textured hair. We explore the biological features of this hair type, and discuss the different methods employed to straighten afro-textured hair, focusing in particular on chemical straightening. We also examine clinical, anthropological, and psychological issues associated with this latter practice. Examples of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…We have also provided data on the hair washing practices of women of African descent, which contrasts to those of Eurasian populations . The reduced frequency of hair washing in our cohort (mean frequency of 17.9 days, increasing to 32.8 days when hair is braided or in a weave) may be a reflection of beliefs about the lower moisture content of afro‐textured hair and hence susceptibility to dryness and breakage with hair washing . Furthermore, some hair grooming practice, e.g.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…We have also provided data on the hair washing practices of women of African descent, which contrasts to those of Eurasian populations . The reduced frequency of hair washing in our cohort (mean frequency of 17.9 days, increasing to 32.8 days when hair is braided or in a weave) may be a reflection of beliefs about the lower moisture content of afro‐textured hair and hence susceptibility to dryness and breakage with hair washing . Furthermore, some hair grooming practice, e.g.…”
Section: Discussionmentioning
confidence: 95%
“…13 The reduced frequency of hair washing in our cohort (mean frequency of 17.9 days, increasing to 32.8 days when hair is braided or in a weave) may be a reflection of beliefs about the lower moisture content of afro-textured hair and hence susceptibility to dryness and breakage with hair washing. 8,15 Furthermore, some hair grooming practice, e.g. heat straightening, may revert on contact with water, 8 and this may also discourage individuals from washing their hair too frequently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of chemical relaxers is a common, culturally ingrained practice in women with afro-textured hair. 13,14 We have demonstrated that the use of chemical relaxers throughout a subject's lifetime was positively correlated with hair loss (OR 2Á58, 95% CI 1Á20-5Á56; P = 0Á016); however, current use of chemical relaxers was negatively associated with hair loss (OR 0Á57, 95% CI 0Á33-0Á98; P = 0Á043). This apparently contradictory finding may be explained by the fact that subjects with established hair loss avoid the use of chemical relaxers.…”
mentioning
confidence: 93%